Business Groups and Corporate Bond Yield: Evidence From Indonesia - Dwita Purwanti (Syntax Literate, 2023)
This research examines the effect of corporate groups on yield spread of corporate bond. The results will show whether group affiliation has significant effect on yield spread when the bonds issued for first time. Research and studies in Indonesia are still limited, especially those that study the effect of company groups on bond yield spread. The research period was taken from the issuance of bonds by non-financial service issuers from 2013 to 2022 with a total of 365 series of conventional bonds issued by 61 issuers from non-financial services companies and banking. The results of this study show that group affiliation has significant effect on the bond’s yield spread.